Decision Support System in Determining Outstanding Teachers in Tutoring Institution Uses The Simple Additive Weighting method. (Case Study : Tutoring Dunia Sausan Kudus) - lestari, ning rahayu (Jurusan Teknologi Informasi Universitas Semarang, 2019)
Tutoring is helping students to get good adjustments in learning situations, so that each student can learn efficiently according to his abilities and achieve optimal development. In tutoring need to need outstanding teachers to produce high achieving students.With the existence of a decision support system, the admin or head of tutoring can determine the instructors who have achievements, and can manage teaching data, employee data safely and efficiently. In this decision support system uses the SAW (Simple Additive Weighting) method. This system was developed using the PHP programming language and MySQL database. The final results of this study found that the SAW (Simple Additive Weighting) method was able to overcome the problems in determining teachers who excel, and can manage teaching data, employee data safely and efficiently. Keywords: Decision Support System, Tutoring, Dunia Sausan Kudus